Definitive radiation therapy without chemotherapy for human papillomavirus–positive head and neck cancer. Issue 11 (17th January 2013) - Chen, Allen M.; Zahra, Talia; Daly, Megan E.; Farwell, D. Gregory; Luu, Quang; Gandour‐Edwards, Regina; Vaughan, Andrew T.
<x xml:space="preserve">Abstract</x> Background To report a single institutional experience with definitive radiation therapy alone for human papillomavirus (HPV)–positive head and neck cancer. Methods A total of 67 patients were treated by radiation therapy alone to a median dose of 70 Gy (range, 66–72 Gy) for squamous cell carcinoma of the head and neck. Paraffin‐embedded, formalin‐fixed pretreatment tumor tissues were used to establish HPV‐positivity using standardized techniques of immunohistochemistry for p16 and polymerase chain reaction for HPV. Results In all, 23 patients with HPV‐positive cancers were identified. With a median follow‐up of 28 months (range, 6–85 months), the 3‐year actuarial rates of overall survival, locoregional control, and distant metastasis‐free survival were 83%, 90%, and 88%, respectively. Conclusion These findings attest to the exquisite radiosensitivity of HPV‐positive head and neck cancer. The clinical outcomes observed from this selected series compare favorably with historical controls treated by more intensive chemoradiotherapy strategies. © 2013 Wiley Periodicals, Inc. Head Neck, 35: 1652–1656, 2013